(untitled) (American Journal of Islam and Society, 2001)
This article attempts to reconceptualize the theories of pluralism, ethnicity and multiculturalism by analyzing the present predicament of Muslims and their mode of organization. However, this cannot be done in isolation from the normative theory, which is grounded in the Islamic sources and worldview. It provides an analytical insight into the interface of unity and diversity and limitation of achieving a haixnonious relationship between them in the modem western societies. Ideals of the westem social theory are critiqued through the Islamic ideals to conceptualize alternative way of socio-political organization.